Artificial Intelligence; Most growing sector of world - Alexandara Harry (Information Technology and Science (ITScience), 2022)
This review article provides an overview of the field of artificial intelligence (AI), including its history, types, techniques, and ethical and societal implications. The article traces the history of AI from ancient times to its formalization as an academic field in the 1950s, and its subsequent progress and setbacks. The different types of AI, including rule-based AI, machine learning, deep learning, and natural language processing, are discussed, along with the techniques used to create intelligent systems, such as neural networks, decision trees, Bayesian networks, and genetic algorithms. The article also explores the ethical and societal implications of AI, such as bias, privacy concerns, and job displacement, and the potential solutions to these challenges.